Visualisation of Amphetamine Contamination in Fingerprints Using TOF-SIMS Technique - Małgorzata I. Szynkowska-Jóźwik (MDPI AG, 2021)
Time-of-flight secondary ion mass spectrometry (TOF-SIMS) was applied to detect traces of amphetamine on fingerprints. In the present study, three different lift tapes and latent powder fingerprints were tested. The obtained results show that it is possible to identify traces of a drug as well as its distribution over the tested fingerprint after its transfer from the primary base onto an adhesive lifter (secondary base). Moreover, images obtained by the TOF-SIMS technique enable the observation of very small areas of the analysed fingerprint as well as the identification of micro-objects (residues of a contaminant) that were left on the fingerprint. The use of the black latent fingerprint powder did not interfere with the TOF-SIMS analysis, which makes it possible to effectively use this technique to study the traces of substances on the revealed fingerprints.